Crystal structure of (3-hydroxy-4-methoxyphenyl)(pyrrolidin-1-yl)methanone, C12H15NO3 - Xu Xiaona; Tong Hongjuan; Zhu Zhoujing; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C12H15NO3, monoclinic, P21/c (no. 14), a = 6.7230(2) Å, b = 11.1182(3) Å, c = 14.4996(5) Å, β = 94.8870(10)°$94.8870(10){}^{°}$, V = 1079.87(6) Å3, Z = 4, Rgt(F) = 0.0511, wRref(F2${F}^{2}$) = 0.1525, T = 170 K.